Konsep ilmu dalam pandangan Abu Al-Hasan Al-‘Amiri - Pandita, Gavrila (Maliki Interdisciplinary Journal, 2024)
The philosophical thought of ancient Greece has had a significant impact on the development of philosophy within the Islamic tradition. Many Muslim scholars were inspired by the works of Aristotle and intrigued by the concepts introduced by Plotinus. This influence extended beyond philosophy, as science continued to evolve with the emergence of thinkers who combined perspectives from both Greek and Eastern traditions, often referred to as Islamic philosophy. One prominent figure in Islamic philosophy is Abu al-Hasan al-'Amiri, who asserted that knowledge and religion do not contradict but rather complement each other. Al-'Amiri argued that epistemology should be guided by the teachings of the Qur'an and Hadith while remaining open to contributions from other sources of thought. Through this perspective, al-'Amiri demonstrated that the integration of science and religion is both possible and necessary for the advancement of human understanding. Al-'Amiri's approach reflects the characteristic of Islamic philosophy that seeks to unify various intellectual traditions within a strong religious framework. This indicates that Islamic philosophy is not merely about the wholesale acceptance of Greek thought but also about the adaptation and integration of these ideas into the Islamic context. Consequently, the Islamic philosophical tradition enriches and expands the existing intellectual horizons while maintaining harmony with the fundamental principles of Islam. In conclusion, the philosophical thought of ancient Greece has become a cornerstone in the development of Islamic philosophy, with figures like Abu al-Hasan al-'Amiri successfully harmonizing knowledge and religion in a constructive manner.